Zur Eigenart der LXX-Manuskripte der b-Gruppe in der Genesis: Spezielle Lesarten, exegetische Textplus/-minus und Berührungen mit der samaritanischen Texttradition - Schäfers, Kirsten (TC, 2024)
In the Greek textual history of Genesis, the so-called b-group stands out with unique readings. These readings received little attention in the last thirty years after John W. Wevers had concluded that the Lucianic text of Genesis cannot be found in this group and most likely never existed at all. This pre-study does not intend to reopen the quest for the Lucianic text. Rather, it opens up new perspectives on the age and relevance of b’s textual tradition against the background of more recent text-historical research. The article argues that not all unique readings in the b-group should be rejected as late and text-historically worthless. First, the current state of research is summarized briefly. Second, the text-historical significance of the b-group is examined by starting from the notoriously difficult Hebrew and Greek text in Gen 21:14. The subsequent analysis focuses on exegetical text pluses as well as conspicuous text minuses and a significant agreement with the Samaritan text tradition. Significant evidence allows for the conclusion that the exegetical text pluses and some conspicuous text minuses of the group have characteristics similar to the early harmonization phenomena attested by SP, LXX and some Qumran-MSS, more broadly also to those attested in the Antiochene Text of other books. For at least one manuscript (Ra 108) there are indications of contact with a Samareitikon tradition. Based on this evidence, an ancient age of many special readings in the b-group can be assumed with good reason. Thus, the text-historical value of this group of manuscripts potentially increases and should be investigated further.